2010
DOI: 10.1007/s12016-010-8224-0
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Dendritic Cells in Atopic Dermatitis: An Update

Abstract: Dendritic cells (DCs) have been recognized as key players bridging innate and adaptive immune systems. They control the balance of the adaptive immune response, and the functional behavior of DCs is mainly dictated by their microenvironment. Atopic dermatitis (AD) is a paradigmatic disease where the inflammatory microenvironment has a deep impact on DCs. The emergence of IgE-mediated sensitization is tightly related to the impact of locally released cytokines by either keratinocytes, T cells, or other cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
(39 reference statements)
1
23
1
Order By: Relevance
“…IFN, interferon; IL, interleukin; mDC, mature dendritic cell; siRNA, small interfering RNACD, cluster of differentiation. the promotion of Th2-cell activation (26)(27)(28). The first signal is the formation of antigen-MHC complexes on the mDC surface that bind specifically with the T-cell receptor-CD3 receptor complex on T-cell surfaces, and the second signal is co-stimulatory molecule expression and functional activation on the mDC surfaces that specifically bind to receptors on naïve T cells; the two signals form a co-stimulatory pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…IFN, interferon; IL, interleukin; mDC, mature dendritic cell; siRNA, small interfering RNACD, cluster of differentiation. the promotion of Th2-cell activation (26)(27)(28). The first signal is the formation of antigen-MHC complexes on the mDC surface that bind specifically with the T-cell receptor-CD3 receptor complex on T-cell surfaces, and the second signal is co-stimulatory molecule expression and functional activation on the mDC surfaces that specifically bind to receptors on naïve T cells; the two signals form a co-stimulatory pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on how this TBI-induced cytokine microenvironment is skewed, it could greatly impact the conditioning of cDC within the skin and dictate how these cells interact with T cells in draining lymph nodes (10). Recently, it has been suggested that atopic dermatitis (AD), a chronic inflammatory skin disease, is, in part, initiated and driven by cDC (41) and patients who suffer from AD often exhibit a type 2 cytokine profile within the skin. However, despite an increased understanding in the immunopathology, AD still remains an idiopathic disease that manifests in individuals with a predetermined genetic background or in those exposed to a variety of environmental stimuli (42).…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism by which genetic polymorphisms of the TLR2 gene causes impact on the binding of TLR2 ligands, such as S. aureus ‐derived proteins, herpes simplex virus, β ‐defensins, and others, leading to an altered function of mDCs in AD remains unclear . Polymorphisms of TLR9 on pDCs expressing the high‐affinity receptor for IgE (Fc ε RI) in AD individuals and the possible cross‐talk between TLR2 and Fc ε RI expressed on mDCs in AD patients may provide interesting insights regarding the role of infections in the regulation of IgE synthesis .…”
Section: Introductionmentioning
confidence: 99%